Pop, Pandemic, Politics: On the "Virtual Social" and Ways of Engagement in Times of Crisis– A Conversation Across Borders and Disciplines. Issue 1 (2nd January 2021) - Butler, Martin; Jeziński, Marek
ABSTRACT: In a dialogic form incorporating perspectives from Germany and Poland, the essay maps the effects of the COVID 19 pandemic on the production, distribution, and reception of popular music, arguing that the virtual realm of social media and sharing platforms allows for alternative ways of engaging with pop. Yet, while this "virtual social" may help overcome social disintegration and foster shared identities through times of crisis, the withdrawal to the digital realm always runs the risk of distracting attention from the actual lines of social and racial demarcation and discrimination that become visible during the pandemic.